Augmented Reality in Arthroplasty: An Overview of Clinical Applications, Benefits, and Limitations. Issue 10 (15th May 2022) - Tanzer, Michael; Laverdière, Carl; Barimani, Bardia; Hart, Adam
Abstract : Augmented reality (AR) is a natural extension of computer-assisted surgery whereby a computer-generated image is superimposed on the surgeon's field of vision to assist in the planning and execution of the procedure. This emerging technology shows great potential in the field of arthroplasty, improving efficiency, limb alignment, and implant position. AR has shown the capacity to build on computer navigation systems while providing more elaborate information in a streamlined workflow to the user. This review investigates the current uses of AR in the field of arthroplasty and discusses outcomes, limitations, and potential future directions.